Infrastructure and Ecosystem Analysis of Creative Craft Industry - Wulandari, Deasy; Sukarno, Hari; Fauziyyah, Salma; Khusna, Khanifatul; Muhsyi, Abdul (Universitas Hayam Wuruk Perbanas, 2022)
The creative industry contributes greatly to the Indonesian economy but the export contribution of Indonesia's creative industry is still weak. Therefore, it is necessary to study the analysis of the ecosystem and infrastructure of MSMEs. The purpose of this study is to analyze the competitive position of the craft cluster creative industry. This type of research is descriptive quantitative research with the simple consisting of the craft cluster SMEs. The sample was taken using multistage sampling method, which consisted of purposive sampling and convenience sampling. Analytical tool used is the BCG Matrix. Competitive position of creative industries can be identified from several aspects, including infrastructure and ecosystem aspects. Competitive position of the infrastructure aspect is known through market share on the horizontal axis of the BCG Matrix and competitive position of the ecosystem aspect is known through market growth on the vertical axis of the BCG Matrix. Based on analysis of the BCG Matrix, the craft cluster is in dog quadrant. Dog quadrant has low infrastructure and low ecosystem conditions. The right strategy to apply to craft clusters to get their products out of the dog quadrant is a defense strategy that includes downsizing, diversification or liquidation.